Role of Midwives on supporting IDA prevention & screening: learning from international guideline/practice & evidence - Mariani Rahayu, Endang; Sitorus, Nova Lidia; Yuningrat, Nova (Ridwan Institute, 2024)
Iron deficiency anemia (IDA) is a significant global health problem, with negative impacts on the health of pregnant women, fetuses, and newborns, including the risk of complications such as preterm birth and low birth weight. Midwives play an important role in the prevention and early detection of IDA through education, nutritional counseling, and routine screening, in accordance with international guidelines that need to be adjusted to the local context and capacity of the health system in each country. This study aims to explore the role of midwives in the prevention and early detection of iron deficiency anemia (IDA) in pregnant women by referring to international guidelines, best practices, and the latest scientific evidence. The results of the revoew aims to discuss that the role of midwives in the prevention and screening of Iron Deficiency Anemia (IDA) is very important as the main service provider during pregnancy and childbirth. By utilizing international guidelines, midwives can improve understanding of effective screening techniques and IDA prevention strategies, such as early identification, iron supplementation, and education for pregnant women. Evidence-based practices implemented by midwives can improve maternal and fetal health and reduce the prevalence of maternal mortality (MMR).